Population ecology of the freshwater turtle mesoclemmys vanderhaegei (Testudines: Chelidae) - Brito, Elizângela Silva; Vogt, Richard Carl; Valadão, Rafael Martins; França, Leonardo Fernandes; Penha, Jerry Magno Ferreira; Strüssmann, Christine (Herpetological Conservation and Biology, 2018)
We sampled Mesoclemmys vanderhaegei in the Upper Paraguay River Basin, in the Cerrado ecosystem of Central Brazil. Populations were sampled between 2010 and 2013, and we used capture-mark-recapture methods to determine the catchability, density, population size structure, and sex ratio of the populations. We sampled two protected areas (Chapada dos Guimarães National Park [CGNP] and Serra das Araras Ecological Station [SAES]) and we captured 300 individuals (77 at CGNP and 223 at SAES) and made 343 recaptures in the two areas. Some individuals were recaptured more than once. We estimated population sizes to be 90 turtles at CGNP and 245 turtles at SAES. Sex ratio was not significantly different from 1:1 at CGNP, whereas at SAES there were more females than males. The population structure varied significantly between the two sampled populations with carapace lengths of turtles at CGNP normally distributed but not at SAES. Although both areas occur within the same ecosystem and are close to each other (180 km straight line distance), the populations possessed distinct demographic characteristics, possibly resulting from local patterns of environmental conditions and biological interactions. © 2018. Elizângela Silva Brito. All Rights Reserved.